Web application for enhancing students' campus life (B) - Ye, Qianhan (Nanyang Technological University, 2022)
The main purpose of this project is to design and build a campus-life enhancement website, dedicated to NTU students and teaching staff. There will be a tutorial discussion forum for students to clarify their doubts with classmates and lecturers/tutors, a notification center for teaching staff to roll out any latest updates regarding the classes, and an interactive campus map, for students to share their thoughts and news in real-time so that they will have a more immersive campus life and make new friends, even under the covid period when in-person contact is limited. Moreover, a deadline notification board and a calendar-embedded to-do list are developed to increase the efficiency of studying. This is a cooperation project carried out by me, Ye Qianhan (Sch of EEE, IEM), and my partner, Li Hang (Sch of EEE, EEE). The website is developed based on the three-tier architecture of web applications: client tier, logic tier, and data tier. For my part, I mainly focus on the client tier and logic tire. For the client tier, I developed a web frontend in javascript and used React framework. For the logic tier, I created a backend-for-frontend(BFF) to better communicate and process the data passing from the backend server, written by nodejs and using the Next.js framework.